2011
DOI: 10.1093/cvr/cvr105
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation protects against ventricular fibrillation independent of muscarinic receptor activation

Abstract: We show that the vagal anti-fibrillatory action in the rabbit ventricle occurs via post-ganglionic efferent nerve fibres, independent of muscarinic receptor activation, VIP, and the endothelium. Together with our previous publications, our data support the possibility of a novel ventricular nitrergic parasympathetic innervation and highlight potential for new therapeutic targets to treat ventricular dysrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
87
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 41 publications
9
87
0
3
Order By: Relevance
“…Based on the fact that the occurrence of fatal ventricular arrhythmias is accompanied by a marked decrease of parasympathetic activity in CHF, some studies demonstrate that decreased parasympathetic activity is correlated with malignant ventricular arrhythmogenesis in the CHF state 11, 46, 47, 48. Recent studies have also found that the parasympathetic activation induced by vagal nerve stimulation prevents fatal ventricular arrhythmias and improves survival rates in animal CHF models 17, 18, 19. However, there is no direct evidence to clarify the role of decreased parasympathetic activity in ventricular arrhythmogenesis and how decreased parasympathetic activity links to ventricular arrhythmogenesis in CHF due to the coexistence of multiple factors in the CHF state (such as sympathetic overactivation, ventricular morphological changes, and others).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fact that the occurrence of fatal ventricular arrhythmias is accompanied by a marked decrease of parasympathetic activity in CHF, some studies demonstrate that decreased parasympathetic activity is correlated with malignant ventricular arrhythmogenesis in the CHF state 11, 46, 47, 48. Recent studies have also found that the parasympathetic activation induced by vagal nerve stimulation prevents fatal ventricular arrhythmias and improves survival rates in animal CHF models 17, 18, 19. However, there is no direct evidence to clarify the role of decreased parasympathetic activity in ventricular arrhythmogenesis and how decreased parasympathetic activity links to ventricular arrhythmogenesis in CHF due to the coexistence of multiple factors in the CHF state (such as sympathetic overactivation, ventricular morphological changes, and others).…”
Section: Discussionmentioning
confidence: 99%
“…However, such pharmacological treatment is not ideal because the ability of β‐adrenergic receptor blockers to affect cardiac vagal activity is limited,15 and survival rates even when β‐blockers are used are lower in CHF patients with depressed cardiac vagal activity than in CHF patients with normal cardiac vagal activity 16. Although modulation of cardiac vagal activation as a potential therapy has received only limited attention, direct cardiac vagal nerve stimulation has been found to suppress ventricular tachyarrhythmia and to improve survival rates in CHF 17, 18, 19. Therefore, exploring the mechanism(s) responsible for the impairment of cardiac vagal function can provide a new therapeutic strategy for eliminating ventricular tachyarrhythmia and reducing related mortality.…”
mentioning
confidence: 99%
“…Experimental and developmental studies of the autonomic cardiac nervous system have also been conducted in animals such as the mouse, rat, rabbit, chick, and dog (Armour et al, 1972;Benítez et al, 1959;Brack et al, 2011;Gomez, 1958;Haws and Burgess, 1978;Hildreth et al, 2008Hildreth et al, , 2009Kirby et al, 1980;Kuratani et al, 1991;Kuratani and Tanaka, 1990;Levy et al, 1966;Mabe and Hoover, 2011;Meyer et al, 2010;Mizeres, 1955Mizeres, , 1957Mizeres, , 1958Mizuno et al, 2010;Oliveira et al, 2010;Roberts, 1991;Schwartz, 2010;Scherlag et al, 2011;Shaner, 1930;Shoba and Tay, 2000;Uchida et al, 2010;Verberne et al, 1998). However, huge differences in the cardiac nervous system between humans and the experimental animals have been recognized (Batulevicius et al, 2003;Brugnaro et al, 2003;Kawashima, 2011;McKibben and Getty, 1968;Rysevaite et al, 2011;Pauza et al, 2002a,b).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence showing that vagal nerve stimulation reduced the incidence of ventricular fibrillation in conscious dogs subjected to cardiac ischemia (58) and that it increased the ventricular fibrillation threshold in hearts from rabbits subjected to coronary artery ligation (7). Furthermore, it has been argued that this antiarrhythmic effect of parasympathetic activity could occur because preventing Cx43 degradation in infarcted hearts, in turn, prevents the cell-to-cell electrical uncoupling of ventricular myocytes (4).…”
Section: Electrocardiographic Responsesmentioning
confidence: 99%